Novel electrophysiological criteria for septal ventricular outflow tract tachycardias requiring a sequential bilateral ablation. (17th November 2017) - Lin, Chin‐Yu; Chung, Fa‐Po; Lin, Yenn‐Jiang; Chang, Shih‐Lin; Lo, Li‐Wei; Hu, Yu‐Feng; Liao, Jo‐Nan; Tuan, Ta‐Chuan; Chao, Tze‐Fan; Chang, Yao‐Ting; Chen, Yun‐Yu; Te, Abigail Louise D.; et al.
Abstract: Background: Septal ventricular outflow tract ventricular arrhythmias (OT‐VAs) are defined as septal origin VAs from the right ventricular or left ventricular OT. Patients with septal OT‐VAs may require a sequential bilateral OT ablation. This study aimed to evaluate the electrophysiological characteristics and ablation outcome in patients with septal OT‐VAs. Methods: We retrospectively analyzed the electrocardiography and electrophysiological parameters in 96 patients (mean age 49 ± 15 years, 49 male) undergoing bilateral activation mapping before catheter ablation of idiopathic septal OT‐VAs. The patients were categorized into three groups based on the successful ablation sites, including the right ventricular outflow tract (RVOT), RVOT/left ventricular outflow tract (LVOT), and LVOT. Results: Mapping in the three groups demonstrated a gradually decreasing and increasing trend in the earliest activation time obtained from the RVOT and LVOT, respectively. The absolute earliest activation time discrepancy (AEAD) of ≤18 milliseconds could predict the requirement for a sequential bilateral ablation with a sensitivity and specificity of 100.0% and 93.7%, respectively. The small AEAD (≤21 milliseconds) was associated with a higher recurrence rate in patients receiving a successful unilateral ablation, while patients with a longer distance between the bilateral OT earliest activation sites (DEA > 26 mm) increased future recurrences after an initially successful sequential bilateral ablation. Conclusions: The application of bilateral OT‐VA activation mapping and the measurement of the AEAD and DEA provided not only pivotal information for the ablation strategy, but also prognostic implications for recurrences in patients with septal OT‐VAs.